PERAN GURU BK DALAM MENGURANGI PERILAKU PROKRASTINASI SISWA MELALUI LAYANAN KONSELING INDIVIDU BERBASIS COGNITIVE BEHAVIORAL THERAPY (CBT) DENGAN TEKNIK GRADED TASK ASSIGNMENT DI SMA NEGERI COLOMADU TAHUN PELAJARAN 2025/2026 - Gladies Elga Putri Fitria; Hera Heru Sri Suryanti; Eko Adi Putro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Gladies Elga Putri Fitria. THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN REDUCING STUDENTS' PROCRASTINATION BEHAVIOR THROUGH INDIVIDUAL COUNSELING SERVICES BASED ON COGNITIVE BEHAVIORAL THERAPY (CBT) WITH GRADED TASK ASSIGNMENT TECHNIQUES IN COLOMADU STATE HIGH SCHOOL IN THE ACADEMIC YEAR OF 2025/2026. Thesis Surakarta: Faculty of Teacher Training and Education, Slamet Riyadi University, Surakarta, 2026. The purpose of this study was to describe the role of Guidance and Counseling (BK) teachers in reducing students' procrastination behavior through individual counseling services based on Cognitive Behavioral Therapy (CBT) with graded task assignment techniques in Colomadu State High School in the 2026 Academic Year. This study was conducted at Colomadu State High School. The subjects in this study were BK teachers and students who experienced procrastination behavior. This study is a descriptive qualitative study conducted in four individual counseling meetings. Data collection techniques included interviews, observation, and documentation. Data analysis utilized data reduction, data presentation, and conclusion drawing, as well as data validity testing through theoretical and technical triangulation. The results of the study indicate that the role of guidance counselors through individual counseling services based on Cognitive Behavioral Therapy (CBT) with graded task assignment techniques is effective in helping students reduce procrastination. This is demonstrated by positive changes in students, such as increased awareness of the impact of procrastination, the ability to identify and evaluate negative thoughts rationally, and the ability to complete tasks in stages and on time. Therefore, individual counseling services based on CBT with graded task assignment techniques can be an effective strategy in reducing procrastination in students.